PENENTUAN UKURAN BLOK OPTIMAL DALAM PRODUKSI KAPAL - Wiwi, Umar
Building ship by block method, block has been done in shop with limited measurement, and carried to building berth for erection by transportation tool with determined capacity. Therefore block size must accord with shop measurement, transportation tool capacity and technical worthiness. Besides this, block can be finished according to due date, and shop working by high effectively. This thesis submitted for optimization model to determine block size with considering all of production constrains directly. This model developed from Single Machine Batch Scheduling Model that suggested by Halim et.al (7,8) by using analogy of batch size became block size and including of technical constrains that connected with ship production. Besides this has been developed also for scheduling block was resulted by thinking of scheduling block problem in parallel machine. Result of this research shows that single machine batch scheduling can be developed to determine optimal block size in shipping industry with pay attention analogy between batch and block. Block size that asserted by number of unit, analogies by block size that determined by length and weight. Nevertheless in model that suggested, block size determined by it weight and weight is function of length and weight intensity. So function be formed among total actual flow time, weight and block length are composite function. Result of this research also shows to minimize total actual flow time of block in assembly shop, the block length in first determination must be equal with construction length that pointed to shop assembly length. In the later it will be investigated and be connected with other constrains. The other conclusion has been received that must be a balance between shop assembly length and transportation tool capacity that accord of both with size of ship.